2004
DOI: 10.1016/j.orthres.2004.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral‐mediated transfer of human BMP‐6 gene accelerates healing in a rabbit ulnar osteotomy model

Abstract: This study evaluated healing of rabbit bilateral ulnar osteotomies 6 and 8 weeks after surgery in response to percutaneous injection of transgenic adenoviral (Ad) bone morphogenetic protein-6 (BMP-6) vector or green fluorescent protein vector control (Ad-GFP) administered 7 days after surgery compared to untreated osteotomy controls. The amount, composition and biomechanical properties of the healing bone repair tissue were compared among groups and to historical data for intact rabbit ulnae obtained from simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 69 publications
1
65
0
Order By: Relevance
“…1,2 A growing literature describes the responsiveness of bone to transfer of osteogenic cDNAs encoding bone morphogenetic proteins (BMPs) -2, -4, -6, -7 and -9. [3][4][5][6][7][8][9] The properties of those BMPs have many potential clinical applications, such as to accelerate the healing of fractures, improve the repair of non-unions and segmental defects, enhance spinal fusion and provide better fixation for prosthetic implants.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,2 A growing literature describes the responsiveness of bone to transfer of osteogenic cDNAs encoding bone morphogenetic proteins (BMPs) -2, -4, -6, -7 and -9. [3][4][5][6][7][8][9] The properties of those BMPs have many potential clinical applications, such as to accelerate the healing of fractures, improve the repair of non-unions and segmental defects, enhance spinal fusion and provide better fixation for prosthetic implants.…”
Section: Introductionmentioning
confidence: 99%
“…3,10 The direct, local injection of adenovirus carrying human BMP-2 cDNA (Ad.BMP-2) heals critical-sized segmental defects in rabbits and rats. 10,11 This vector also accelerates the healing of tibial fractures in osteoporotic sheep, 12,13 and Ad.BMP-6 accelerates the healing of tibial fractures in rabbits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The off-label use of recombinant BMP has led to complications including local edema, resorption of surrounding bone, and ectopic bone formation, as seen in multiple animal models in the setting of ON of the femoral head [23•, 27]. Likewise, studies have shown that cellmediated gene therapy approaches have been found to be more efficient at delivering growth factors [36,37,66]. Although vector-mediated cell-based therapy has shown promise in animal models, the transition to clinical trials is potentially limited in a nonlife-threatening disease such as ON due to the complications previously seen with their use, including death and lymphoproliferative disorders [67][68][69].…”
Section: Limitations Of Ancillary Factorsmentioning
confidence: 99%